Pengembangan Unit Usaha Nugget Sehat di Politeknik Negeri Lhokseumawe - Zahra Fona; Eka Kurniasih; . Raudah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
This program aimed to develop nugget sehat products which are no additives content such as synthetic preservatives, stabilizers, and dyes, into a commercial business unit within the auspices of the State Polytechnic of Lhokseumawe (PNL). This program become a basis of practical to students in the nugget production, as well as practical place for fresh graduated alumni before going to the real work. In additon, it become an example of enterpreneurship unit in PNL campus environment. The development includes increasing the production capacity from 3 kg/week to 30 kg/week by this program. It shows a significantly increase of production capacity up to 90%. Before, it was produced only chicken nugget, by this program, there are 3 flavours have been produced: chicken, fish, and vegetable. The promotion was performed not only by direct offering, but also using social media (facebook and bbm). The marketing of the product has reached Lhokseumawe City, Aceh Utara, Aceh Timur, and Banda Aceh. Market place become a problem, due to the limited expired of nugget product in room temperature. Therefore, the particular transportation of the product will be required in order to reach wider area. Moreover, there are 8 students have performed the nugget production in his unit during 2016, and 8 fresh graduated alumni have done the practical work in this unit. Additionally, the society have some benefit by this program, 5 people become the employees and they get knowledge of production sistem base on apllication of technology. In the next stage when the continuity of production running well, the Good Manufacturing Practice (GMP) and Hazard Analysis Critical Control Point (HAACP) can be implemented in this business unit.